Inequality in the Regional Distribution of Employment Insurance Benefits in Canada - Hoyi, Dela y. (Université d'Ottawa | University of Ottawa, 2009)
Employment insurance (EI) has been an important feature of Canada's income security system since 1940. The program has evolved over the years to adjust to changes in the composition of the, not to mention political pressure, labour force and economic acti